2020
DOI: 10.1186/s12935-020-01291-y
|View full text |Cite
|
Sign up to set email alerts
|

SNHG16 promotes tumorigenesis and cisplatin resistance by regulating miR-338-3p/PLK4 pathway in neuroblastoma cells

Abstract: Background Long noncoding RNA small nucleolar RNA host gene 16 (lncRNA SNHG16) has been revealed to be involved in the tumorigenesis of neuroblastoma. However, the role of SNHG16 in regulating cisplatin sensitivity in neuroblastoma remains largely unknown. Methods The expression of SNHG16, microRNA (miR)-338-3p and polo-like kinase 4 (PLK4) mRNA was measured using quantitative real-time polymerase chain reaction. The protein levels of PLK4, multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Expression of P-gp protein in neurons has been a point of contention. For example, several groups have demonstrated P-gp expression in neuronally-derived cell lines [ 35 , 36 , 37 , 38 ] and on peripheral nerve tissue at the blood-nerve-barrier (BNB) [ 39 , 40 , 41 ], whereas others have failed to do so or have demonstrated that it is only expressed in the context of brain injury or pathology [ 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Expression of P-gp protein in neurons has been a point of contention. For example, several groups have demonstrated P-gp expression in neuronally-derived cell lines [ 35 , 36 , 37 , 38 ] and on peripheral nerve tissue at the blood-nerve-barrier (BNB) [ 39 , 40 , 41 ], whereas others have failed to do so or have demonstrated that it is only expressed in the context of brain injury or pathology [ 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…15.99 Down-regulated in resistant NB [77,78] Down-regulated in esophageal squamous carcinoma cells [79] miR-497 6.92…”
Section: Resultsmentioning
confidence: 99%
“…In detail, miR-27b and miR-16-1 expression levels were found to be reduced by 33.1 and 23.5 fold, respectively, and miR-218 expression was diminished by 9.09 fold, while miR-15a, miR-126, and miR-19b were down-regulated (slightly, but significantly) by 2.8, 2.7, and 1.73 fold, respectively. [59], gastric [60,61], and ovarian [62,63] cancer, and osteosarcoma [64] miR-126a 9.66 Not evaluated Down-regulated in colorectal [65] and breast cancer [66] and in renal cell carcinoma [67] miR-218 12.30 Up-regulated in MYCN-amplified and in metastatic NB [68][69][70] Down-regulated in glioma cells [71], colorectal [72], gallbladder [73], bladder [74], and lung cancer [75,76] miR-338 15.99 Down-regulated in resistant NB [77,78] Down-regulated in esophageal squamous carcinoma cells [79] miR-497 6.92…”
Section: Resultsmentioning
confidence: 99%
“…Recent work uncovered that PLK4 was a downstream effector of the SNHG16/SNHG1/miR-338-3p axis in regulating NB progression. 32,33 Tian et al demonstrated that PLK4 accelerated NB cell epithelialmesenchymal transition process by activating the PI3K/ Akt signaling, which was implicated in NB carcinogenesis. 34,35 Additionally, direct evidence of the novel mechanism in tumor growth in vivo was absent, which will be conducted in further work.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we showed that DLX6‐AS1 functioned as a posttranscriptional regulator of PLK4 expression by sponging miR‐513c‐5p. Recent work uncovered that PLK4 was a downstream effector of the SNHG16/SNHG1/miR‐338‐3p axis in regulating NB progression 32,33 . Tian et al demonstrated that PLK4 accelerated NB cell epithelial–mesenchymal transition process by activating the PI3K/Akt signaling, which was implicated in NB carcinogenesis 34,35 .…”
Section: Discussionmentioning
confidence: 99%